2006
DOI: 10.1007/s00125-006-0475-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired in vivo mitochondrial function but similar intramyocellular lipid content in patients with type 2 diabetes mellitus and BMI-matched control subjects

Abstract: Aims/hypothesis Mitochondrial dysfunction and increased intramyocellular lipid (IMCL) content have both been implicated in the development of insulin resistance and type 2 diabetes mellitus, but the relative contributions of these two factors in the aetiology of diabetes are unknown. As obesity is an independent determinant of IMCL content, we examined mitochondrial function and IMCL content in overweight type 2 diabetes patients and BMI-matched normoglycaemic controls. Methods In 12 overweight type 2 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
227
8
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(261 citation statements)
references
References 31 publications
15
227
8
1
Order By: Relevance
“…When mitochondrial activity was determined per muscle weight (i.e. muscle oxidative capacity), studies have either shown no differences [3][4][5] or a lower [6][7][8][9][10][11][12] mitochondrial activity in insulin-resistant participants. Studies that have related mitochondrial activity to markers of mitochondrial volume (intrinsic mitochondrial activity) have either shown a lower [6,12,13] or no difference [9-11, 14, 15] in mitochondrial activity in insulin-resistant participants.…”
Section: Introductionmentioning
confidence: 99%
“…When mitochondrial activity was determined per muscle weight (i.e. muscle oxidative capacity), studies have either shown no differences [3][4][5] or a lower [6][7][8][9][10][11][12] mitochondrial activity in insulin-resistant participants. Studies that have related mitochondrial activity to markers of mitochondrial volume (intrinsic mitochondrial activity) have either shown a lower [6,12,13] or no difference [9-11, 14, 15] in mitochondrial activity in insulin-resistant participants.…”
Section: Introductionmentioning
confidence: 99%
“…An alternate 31 P-magnetic resonance spectroscopy technique, based on exercise recovery experiments, has been used extensively to investigate mitochondrial function in various phenotypes (7,8) and more recently also in insulin resistance and T2DM (9,10). Purely aerobic, mixed, or anaerobic exercise is used to deplete PCr.…”
Section: Introductionmentioning
confidence: 99%
“…The recently published results of de Feyter et al (17) did not show an effect of insulin resistance or type 2 DM on mitochondrial function when compared to healthy normoglycemic controls, which is in accordance with our study results. In the current study we did not perform proton MRS to further evaluate mitochondrial dysfunction and the association with insulin resistance, as shown in previous studies (15,17). Thus, the exact relationship between DM per se and skeletal muscle phosphate metabolism remains to be clarified, but our results clearly indicate an effect of the MIDD mutation itself on phosphate metabolism.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, Schrauwen-Hinderling et al (15) applied 31 P-MR spectroscopy in the vastus lateralis muscle to study mitochondrial function in overweight type 2 DM patients and BMI-matched control subjects. They reported a longer PCr recovery half-time in the type 2 diabetes group when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation